Details for Glaucous Gull at Lock and Dam 14 in Davenport in 1992 - Fuller, James Let al (1992)
Field notes by Jim Fuller for a Glaucous Gull at Lock and Dam 14 in Davenport on January 5, 1992. Epson - sheet feed